2016
DOI: 10.1097/phm.0000000000000353
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Functioning of Patients with Aneurysmal Subarachnoid Hemorrhage

Abstract: Many patients with aneurysmal subarachnoid hemorrhage had fairly good long-term outcomes, but problems in executive functioning, mood, and fatigue still exist at long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 27 publications
1
10
0
1
Order By: Relevance
“…Moreover, some research suggests that increased SWS is found among patients with chronic fatigue syndrome [76,77]. Thus, the fact that a relatively large portion of aSAH patients (50-70%) suffer from severe and stable fatigue symptoms [7,8,30,78] might explain why deep sleep is increased in this patient group. In other words, in aSAH patients, long S4 sleep might rather be an indication of chronic fatigue than of restoring sleep, although the absence of a measure of chronic fatigue in this study means that this observation cannot be confirmed for the present sample.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, some research suggests that increased SWS is found among patients with chronic fatigue syndrome [76,77]. Thus, the fact that a relatively large portion of aSAH patients (50-70%) suffer from severe and stable fatigue symptoms [7,8,30,78] might explain why deep sleep is increased in this patient group. In other words, in aSAH patients, long S4 sleep might rather be an indication of chronic fatigue than of restoring sleep, although the absence of a measure of chronic fatigue in this study means that this observation cannot be confirmed for the present sample.…”
Section: Discussionmentioning
confidence: 98%
“…Boerboom et al [7] examined 76 patients following treatment and at 4-year follow-up, and found that while some measures improved, depression scores remained constant. Elevated levels of depression, even several years post-ictus, have been documented in another study [8], and numerous articles report mild-to-moderate depression rates of between 14 and 39% in this population [9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In order to identify the stimulus features that optimally discriminate between bursts of different duration, we turn to multi-discriminant analysis (MDA) (Duda et al, 2001 ; Kepecs and Lisman, 2003 ). The criterion to define the optimal discrimination is based on Fisher's Linear Discriminant (Fisher, 1936 ).…”
Section: Methodsmentioning
confidence: 99%
“…With a mean age of onset between 55 and 57 years, a comparatively young population is affected by this form of stroke [3], and difficulties in resuming normal life following aSAH have been widely documented. Depression [4-6], anxiety [5, 7], post-traumatic stress disorder [8, 9], and concerns about sleep (that is, worries and negative attitudes to sleep duration and quality) [8, 10] were chief among the psychiatric disorders and deficits in well-being reported by patients following aSAH. Some studies have also found sleep disorders during objective sleep assessment [10], although others have reported no deficits in this domain, in spite of poor subjectively assessed sleep [11].…”
Section: Introductionmentioning
confidence: 99%